Intertemporal MPC and shock size - Tullio Jappelli; Ettore Savoia; Alessandro Sciacchetano (Sveriges Riksbank, 2024)
We elicit the intertemporal Marginal Propensity to Consume (iMPC) based on hypothetical different size lottery winnings through questions in the 2023-24 Italian Survey of Consumer Expectations (ISCE). Survey respondents were asked to allocate three hypothetical lottery winning amounts ( exteuro1,000, exteuro10,000. and exteuro50,000) between consumption and saving in both the year following the survey and over the longer term. The iMPC for a exteuro1,000 win declines from 26% in the first year to about 1% five years after the shock. Larger win amounts have a smaller impact in the first year and a larger impact in the long run. The iMPC for a exteuro10,000 ( exteuro50,000) prize declines from 19% (15%) in the first year to 2.5% (4%) in year five. Regardless of the size of the shock, the iMPC shows a weak negative relation to the cash-on-hand amount and a negative relation to income risk. We show that calibrated simulations of incomplete market models with borrowing constraints, income risk, and household heterogeneity are broadly consistent with these empirical findings.
Keywords: D12; D14; D15; C8; C99; 330; Intertemporal Marginal Propensity to Consume; Income Shocks; Shock Size